Diathesis Markings in Haloban Language: A Linguistic Typological Study - Syarifuddin; Nasution, Khairina; Mulyadi; Setia, Eddy (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2024)
This research aims to explore, analyze, and explain the Haloban language's linguistic phenomena, including morphological typology and argument structure. This research also seeks to enrich the linguistic treasures of the archipelago. This study applies the theory of diathesis proposed by Lyon. It adopts a qualitative descriptive method where comparative and inductive treatment is carried out on the data collected through a phenomenological approach. The data used in this study is oral data collected from 73 informants who live in Haloban and Asantola Village. This study shows that the Haloban language has a marking active-passive diathesis, one of the essential characteristics in the typology of accusative language. In addition to having an active-passive diathesis, the Haloban language also has a medial diathesis. From the perspective of linguistic typology, the Haloban language's active and passive diathesis shows a significant difference when compared to a diathesis in accusative language. Haloban has two types of passives: passive ni- and passive pronouns. Based on the marking system, the morphologically marked passive construction ni- has an active form, which is also morphologically marked. In passive construction, verbs that indicate passive diathesis are marked by the prefix ni-, while verbs that indicate active diathesis are marked by the prefix {ma-}. Syntactically, the active diathesis subject in the diathesis functions as an adjunct in the form of a prepositional phrase and can be removed. In the construction of passive pronouns, verbs that indicate passive diathesis appear as a base verb, while verbs that indicate active diathesis are marked by the prefix {ma-}. Agents in passive pronoun clauses cannot be omitted. This shows that active diathesis is more marked in passive pronouns than passive diathesis.